MYBIOTA: a birth cohort on maternal and infant microbiota and its impact on infant health in Malaysia - Eow, Shiang Yen; Gan, Wan Ying; Jiang, Tiemin; Loh, Su Peng; Lee, Ling Jun; Chin, Yit Siew; Thian, Leslie Lung Than; How, Kang Nien; Thong, Pui Ling; Liu, Yanpin; Zhao, Junying; Chen, Lijun (Frontiers Research Foundation, 2022)
Background: The microbiota plays a key role in early immunity maturation that affects infant health and is associated with the development of non-communicable diseases and allergies in later life. Objective: The MYBIOTA is a prospective mother-infant cohort study in Malaysia aiming to determine the association between gut microbiota with infant health (temperament, gastrointestinal disorders, eczema, asthma, and developmental delays) in Selangor, Malaysia. Methods: Pregnant mothers will be enrolled in their first trimester of pregnancy, and follow-ups will be done for infants during their first year of life. Maternal-infant biological samples (blood, feces, saliva, urine, and breast milk), anthropometric, dietary, and clinical information will be collected at different time points from early pregnancy to 12 months postpartum. Discussion: This study could provide a better understanding of the colonization and development of the gut microbiome during early life and its impact on infant health. Clinical trial registration: https://clinicaltrials.gov/, identifier NCT04919265.